The Identification of Several Dipterocarpaceae and Fagaceae Trees by Barcode DNA Coupled with High-Resolution Melting Analysis - Maslin Osathanunkul (MDPI AG, 2021)
The loss of forests is a major environmental, social, and economic problem. The disappearance has been occurring to an extreme degree in many parts of Southeast Asia, including Thailand. Logging and clearing of forests for agriculture, cash crops, and food production has destroyed much of the tropical forests in Thailand. Floristic inventory could provide essential information for forest conservation but species identification as a part of inventory creating could be challenging in some cases. Barcode DNA coupled with High Resolution Melting analysis (Bar-HRM) was used here in aiding species identification of plant in Dipterocarpaceae (Dipterocarpus alatus, D. costatu, D. intricatus, D. obtusifolius, Hopea ferrea, H. odorata, Shorea guiso, S. obtuse, S. roxburghii, and S. siamensis) and Fagaceae (Castanopsis echinocarpa, C. inermis, Lithocarpus wallichianus, Quercus aliena and Q. oidocarpa) families. Two main experiments were conducted including: (1) a comparing method for primer design and (2) testing the robustness of the Bar-HRM by trying to identify tree samples that did not have sequences in the GenBank. In experiment 1, the manual design primer pair was found to be the best fit for the work. Of key importance is finding the primers which give the most nucleotide variations within the generated amplicon; this is a parameter that cannot be set in any web-based tools. Next, in experiment 2, Bar-HRM using primers of ITS1 and ITS2 regions were able to discriminate all 10 tested tree species without any problem, even when there were no sequences of the samples to be analysed before performing the HRM. Here, Bar-HRM poses potential to be a game-changer in tropical forest conservation, as it will be useful for species identification.